Śrīcaitanya-mata : Śrīcaitanya Mahāprabhuke darśana aura bhakti-siddhāntakā gaveshaṇātmaka adhyayana - Kapoor, O. B. L. (Paramārtha Prakāśana, 1981)
Philosophy and religion of Chaitanya, 1486-1534, Vaishnava leader from Bengal.